INTEGRATING GENERATIVE AI INTO ART PEDAGOGY - Tak, Trapti; Gupta, Mridula; Gupta, Priya; Khalique, Fehmina; Bajpai, Priya; Aggarwal, Prateek; Jadhav, Tushar (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The present paper suggests an all-encompassing model of applying the Generative Artificial Intelligence in art education in the form of Hybrid Pedagogical Model of AI-Art Learning (HPM-AI). The model reformulates creativity as a collaborative activity between the human intent and algorithmic production, focusing on reflective learning, ethical consciousness and open participation. The analysis of the study brings together the cognitive theory, computational modeling, as well as case-based validation, which is why the study proves that generative AI can improve the diversity of creativity but without cultural and moral responsibility. Three contexts of implementation that included an AI-based design studio, a course on digital heritage restoration, and community-based art workshops were evaluated to determine the flexibility of the framework and its effect on pedagogy. Quantitative visualizations and qualitative thoughts show that HPM-AI contributes to different educational goals in settings: the conceptual innovation of studio learning, the cultural integrity of the practice of restoration, and the inclusive creative empowerment of the learning environment. The paper also discusses implications on authorship, data ethics, and psychology of the learner, that AI should not be viewed as a substitute to artistic skill, and instead it is an intelligent companion, which reflects and magnifies human imagination. The paper concludes, that the ethical design of generative AI in creative education, interdisciplinary faculty development and institutional transparency are the necessary conditions of sustainable integration. HPM-AI framework, therefore, promotes an image of symbiotic creativity, placing art pedagogy on a crossroad of human cognition in relation to cultural continuity in connection with the computational intelligence.